2014
DOI: 10.1177/1545968314547767
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Covert Cognition in Noncommunicative Patients With Severe Brain Injury?

Abstract: Background. Despite recent evidence suggesting that some severely brain-injured patients retain some capacity for topdown processing (covert cognition), the degree of sparing is unknown. Objective. Top-down attentional processing was assessed in patients in minimally conscious (MCS) and vegetative states (VS) using an active event-related potential (ERP) paradigm. Methods. A total of 26 patients were included (38 ± 12 years old, 9 traumatic, 21 patients >1 year postonset): 8 MCS+, 8 MCS−, and 10 VS patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…This suggests that the P300 in paradigms including passive and active conditions may support the detection of voluntary information processing in DOC. A more recent study, however, advises a cautious interpretation of these findings as volitional top-down attention can be impaired in patients with covert cognition (Schnakers et al, 2014). This questions the specificity of the task as it could lead to false negative results.…”
Section: Studying Consciousness Using Passive Stimulation and Active mentioning
confidence: 99%
“…This suggests that the P300 in paradigms including passive and active conditions may support the detection of voluntary information processing in DOC. A more recent study, however, advises a cautious interpretation of these findings as volitional top-down attention can be impaired in patients with covert cognition (Schnakers et al, 2014). This questions the specificity of the task as it could lead to false negative results.…”
Section: Studying Consciousness Using Passive Stimulation and Active mentioning
confidence: 99%
“…However, it has been observed that in a certain population of patients, the capacity for consciousness remains undetectable, even by flawlessly performed behavioural testing, and covert cognition, i.e., signs of wilful brain activity may be revealed in a small percentage of patients that respond mentally to active neuroimaging or electrophysiological paradigms, despite the lack of any behavioral response [13,14,15]. Therefore, multiple studies have been aimed at optimising chronic DOC differential diagnosis and outcome prediction using several neuroimaging techniques, for example, cerebral 18 F-FDG PET, which was shown to complement bedside examinations and predict long-term recovery of patients with UWS [16].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in neuroscientific methodology has led to optimism regarding potential clinical utility in diagnostic and prognostic considerations in patients with DoC, [22][23][24] in part due to several studies indicating that cognitive processing can be detected with imaging techniques in the absence of behavioral signs of consciousness. 5,[25][26][27][28][29] These studies applied tasks that require subjects to exert mental responses to command, 30,31 in contrast to merely passive paradigms eliciting only "automatic" responses. Hence, in order to infer consciousness, it is necessary to include tasks involving active cognitive processing in combination with 6 functional neuroimaging-and electrophysiological methods.…”
Section: Clinical Diagnostic Utility Of Electrophysiological Methods mentioning
confidence: 99%